Unravelling the tapestry: Cross-cultural insights into intelligence and creativity - Vlada Alekseevna Repeykova; Anatoliy Vladimirovich Kharkhurin; Sergey Rostislavovich Yagolkovskiy (PLoS ONE, 2025)
Literature suggests multiple relationships between creativity and intelligence, each supported and contradicted by empirical evidence. The current study investigated cultural variations in the relationship between divergent thinking (DT) and fluid intelligence (Gf). Study participants were students from the most reputable universities in Russia (N = 53) and the United Arab Emirates (UAE; N = 53). The DT test measured their creative potential, the Abbreviated Torrance Test for Adults (ATTA), from which five indicators were extracted for further analyses: composite Creativity Index (CI), fluency, originality, elaboration, and flexibility. The Culture Fair Intelligence Test (CFIT) assessed participants’ Gf. We found a significant negative relationship between Gf score and CI, fluency, elaboration, and flexibility. The results suggest a non-linear trend, which was addressed accordingly. Adding a cultural component into the model explained substantial variance in DT and Gf scores. The Russian sample outperformed the UAE sample on all DT components, while the UAE sample outperformed the Russian sample on the Gf. Samples were different, predominantly on the fluency component, and were more similar in originality. Overall, results suggest the complex interplay between DT and Gf in cross-cultural settings.